Output power fluctuations of distributed photovoltaic systems across an isolated power system: insights from high‐resolution data. Issue 19 (16th February 2021) - Moghbel, Moayed; Glenister, Simon; Shoeb, Md Asaduzzaman; Edwards, David; Calais, Martina; Shahnia, Farhad; Carter, Craig; Stephens, David; Jones, Luke; Trinkl, Pierce
Abstract : Deployment of distributed energy resources has rapidly increased during the last few years. The uptake of renewable energy and especially photovoltaic (PV) systems are of interest to utilities in remote and rural areas where the use of conventional power generation is costly. Investigating the effects of such PV systems on isolated power systems at different penetration levels is a relevant research topic. This study reports on the data acquisition system deployed in a remote town in Western Australia and presents some of the findings and observations extracted from the captured real data. It highlights the maximum PV output variations and investigates the underlying factors. The impact of the PV systems on the voltage across the network is also analysed in this study. The studies show that inverter tripping events have led to larger PV output variations in shorter intervals while the cloud movements have contributed to variations in longer intervals.